The Determinant Factors in the Policy Formulation Process for the Regional Revenue and Expenditure Budget - Baharuddin Andang; Sunandar Ali (Universitas Negeri Makassar, 2022)
The new paradigm for implementing regional autonomy in Indonesia is basically based on the principles of local democracy and good governance. With this basis, the regional government and the Regional People's Representative Council as local institutions are responsible for the implementation of regional autonomy as a manifestation of local community representation. The shift of power from the center to the regions and the empowerment of the Regional People's Legislative Assembly has formed its own dynamics in the interaction relations of the two institutions so that it is often colored by conflicts that have political compromises in the process of formulating and discussing the General Policy on Budgets-Priorities of Budget Ceilings and Draft Regional Revenue and Expenditure Budgets. . Therefore the formulation of the problem in this study is: What are the determinant factors in the policy formulation process for the 2019 Regional Budget for Fiscal Year in Sidenreng Rappang Regency?. This study aims to: Know the determinant factors in the policy formulation process of the Regional Revenue and Expenditure Budget for the 2019 Fiscal Year in Sidenreng Rappang Regency. This study used a qualitative approach with data collection techniques through in-depth interviews and documentation studies. The results of the study show that the determinant factors in the policy formulation process for the Regional Revenue and Expenditure Budget for the 2019 Fiscal Year are: (a) Political factors, (b) the interest of policy-making actors, (c) Capacity factors of policy-making actors, (d) Organizational experience factors of formulating actors and (e) Bargaining of policy formulating actors.